Peran Multimedia Interaktif Dalam Pembelajaran Digital: Kajian Literatur Dan Implementasi Evaluasi : Pendahuluan, metode, hasil, kesimpulan - Ali Ikhwan; Anisa Sri Rahma; Shifa Dwi Lirinzha; Abdul Malik (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The development of information technology has encouraged the implementation of digital learning across various levels of education. One of the innovations widely used is interactive multimedia, which integrates text, images, audio, video, animation, and user interaction into the learning process. This study aims to analyze the role of interactive multimedia in supporting digital learning and its implementation in learning evaluation. The research employed a literature review method using a qualitative descriptive approach. Data were collected from national journal articles and scientific proceedings published between 2021 and 2025 through Google Scholar. Data analysis was conducted through identification, selection, and literature synthesis stages. The results indicate that interactive multimedia contributes to improving learning motivation, understanding of learning materials, student participation, and the effectiveness of learning evaluation. The implementation of interactive multimedia through a quiz application also demonstrates that interactivity and feedback features can support a more effective evaluation process. Therefore, interactive multimedia can be considered an effective solution for enhancing the quality of digital learning.